Estrategia didáctica “Aula laboratorio” y su influencia en el aprendizaje del área de ciencia tecnología y ambiente en estudiantes del 3er de secundaria de la I.E N°00925 Santa Isabel - Arévalo Del Aguila, Sarita (2011)
The investigation called "Didactic Strategy Classroom Laboratory" and ·his, ·iflfltJence ·in the ·learn1ng, -of ·Hle' Area of · Science, Teehno~ogy and, · -En:vi.ror:~ment -in students of tnethifd,-degr.ee,-of -the--levef,of-Secondary Educatiorl of the Educationallnstitution N ° 00925 - Holy lsabeJ, distrid of New Cajamarca in the year 2010. There has for aim determine the influence of the "Didactic Strategy Classroom - l-aboratory!' 'Ít'l- the· ,~eanl}ing· of tne Ares- of Science·,· TeohAolog·y and Environment in the pYpils- of. the third- degree of the level- of Secondary Education~ ~t -is- -necessary to, +ndicate· that the- ·object of st~;~dy· of the probfem takes- root ~n proposing the didactic str.ategy "Ctassroom - -L-abor.atory" that tRey- attow the teachers of Science. T echnology and En.vironment, to. optimize his pedagogic labor. As well as diversa studies have been realizad it brings classroom - ~aboratory over of tne· model ,im~lemer~tation- and· methodological .strategies- r,etated to- the " DJdact~c Str:ateg.y " Ül the precedents- of the investigation, which we find to~ Arévafo And Ofortegui (2005),. Montesa and Cross (2005) Etc. On the, ·basis of the ·theories, -of. the, ·learning'; that you St.Jstain to, the " Oidactic. St.r.ateg;y Classr:oom laboratory ", we, f.ind the'"activ~ teaming, feaming,. for discovery., significant learning and the sociocultural theory,, which the.y influence significantly in the learning of the area of Science, Technology and Env1ronment ,in· the· pupHs of the- thir<l degree of tne 4evel· of Secondary· Education, of the Educationaf. Holy tnstitut.ion- tsabef. of the district of New Cajamarca. in the year 2010. To determirte ·the· above· mentioned ·influence, it was- necessary to -know -the; -leve!, of -leaming -of the, students, that they pr-eseAted, befar-a and after the. · application of the strategy, for what the investigation behaved under a design cuasi experimentally with 19 students of the group control and 20 of the ,exper4mer~tal· g'fol